Pengembangan Sistem Informasi Manajemen Inventori Berbasis Web Menggunakan Framework Laravel (Studi Kasus Warung Berkah) - Adjie Arrayan Surya Putra; Ade Andri Hendriadi; Azhari Ali Ridha (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Warung Berkah still manages its inventory manually, resulting in difficulties in stock recording and monitoring. This study aims to design and develop a web-based Inventory Management Information System using the Laravel framework to support more effective and structured inventory management. The research employed the Waterfall method, consisting of requirements analysis, system design, implementation, testing, and maintenance. The system was developed using Laravel and MySQL and includes features for item management, stock-in and stock-out transactions, inventory reporting, forecasting using the Moving Average method, and Reorder Point (ROP) calculation. The results show that the system was successfully implemented according to the operational needs of Warung Berkah. The system applies the FIFO method in stock-out transactions, resulting in more structured inventory movement data and supporting restocking recommendations through forecasting and ROP calculations. User Acceptance Test (UAT) results indicate a user acceptance rate of 91.4%, which is categorized as very good..